Application Of Prototyping Methods In Web-Based Student Application Development - Baginda Harahap; Solianna Harahap (Jurnal Serumpun Teknik Informatika, 2025)
This study discusses the application of the Prototyping method in the development process of a web-based student attendance application. The purpose of this study is to produce a system that is easy to use by teachers and students in recording attendance in real-time. By using the Prototyping method, developers can create a preliminary design of the application, receive input from users, and then refine the design until the system meets the requirements. The results of the study show that the Prototyping method can accelerate the development process and increase user satisfaction with the application created.